Assessing the Complexity of Decarbonised Power Systems as a Means Towards a Sustainable Society: Trends and Hotspots - Momete, Daniela Cristina (European Journal of Sustainable Development, 2024)
This paper aims to assess the complexity of decarbonized power systems by mapping the trends in the field of low carbon electricity over the period 2000-2023 employing an analysis of the scientific publications. This paper addresses the power sector as it plays an essential role in supporting global efforts towards a sustainable society. The paper provides an overview of decarbonised electricity trends by a quantitative analysis of publications, extracted from Dimensions database and explores relevant literature employing VOSviewer as a visualisation tool. The scientometric analysis reveals the main literature streams by using a semantic map, citation and co-citation analyses. The paper shows an increased preoccupation in the field, starting with 2000, and reveals the most relevant works. Moreover, by aggregating bibliometric data, the paper uncovers the social networks associated with the field and points the interested researchers towards the most influential works. By doing so, the paper provides a better understanding of the complexity of the field of decarbonised power system and allows the identification of current research directions and paves the way towards future research paths. Keywords: sustainable development, decarbonised power, quantitative research; climate change